Pengaruh Webqual Pada Klik Indomaret Dan Gaya Hidup Terhadap Keputusan Pembelian Pada Indomaret Bukit Sukasari Karawang - Alfin Raka Pradana; Netti Nurlenawati; Dexi Triadinda (Journal of Economic, Bussines and Accounting (COSTING), 2024)
PT Indomarco implements new innovations in the form of online application services through Klik Indomaret as a form of implementing technological developments. The aim of this research is to see the influence of Klik Indomaret webquals and lifestyle on purchasing decisions at Indomaret Bukit Sukasari. This research was conducted on 65 consumers or users of the Klik Indomaret Bukit Sukasari application. The explanatory survey method was used in this quantitative research. The primary data used comes from a questionnaire filled out by respondents on Google Form. The sampling technique in this research uses a saturated sampling technique. The data analysis method uses multiple linear analysis in SPSS 27. The analysis findings show that webqual and lifestyle simultaneously have a significant positive influence on purchasing decisions. Meanwhile, lifestyle has the biggest influence at Indomaret Bukit Sukasari in making purchasing decisions.